# Generating functions for tail length and rho-length

I am trying to obtain generating functions for tail length and rho length of a random point in a random mapping.

Let $\phi:\{1,2,\ldots,n\}\to \{1,2,\ldots,n\}$ be a random function. Consider the directed graph whose nodes are the elements $\{1,2,\ldots,n\}$ and whose edges are the ordered pairs $(x,\phi(x))$, for all $x\in \{1,2,\ldots,n\}$. We start from any $u_0$ and keep iterating $\phi$, i.e. we consider the sequence $u_1=\phi(u_0), u_2=\phi(u_1), \ldots$. In fact, starting from any $u_0$, the iteration structure of $\phi$ is described by a simple path that connects to a cycle. The length of this path (measured by the number of edges) is called the tail length of $u_0$ and is denoted by $\lambda(u_0)$. The length of the cycle (measured by the number of edges or nodes) is called the cycle length of $u_0$ and is denoted by $\mu(u_0)$. We also call rho-length of $u_0$ the quantity $\rho(u_0)=\lambda(u_0) +\mu(u_0)$

In the paper entitled “Random mapping statistics” and in the Theorem 3, the authors obtained the expectations for these parameters. How we can obtain generating functions for these parameters?

#### Solutions Collecting From Web of "Generating functions for tail length and rho-length"

Let me point out that the cited paper is a landmark brilliant event
containing profound insights that surpass the MSE question answer
format.

As an example we do the calculation of the expected cycle length
$\mu(u_0)$ and the tail length $\lambda(u_0)$ using the labelled tree
function. We refer the reader to the paper as regards the
asymptotics.

We will provide a closed form of the exponential generating function
of the quantities that are involved.

The species of labelled trees has the specification
$$\mathcal{T} = \mathcal{Z} \times \mathfrak{P}(\mathcal{T})$$
which gives the functional equation
$$T(z) = z \exp T(z).$$

We have that $$T(z) = \sum_{n\ge 1} n^{n-1} \frac{z^n}{n!}.$$

Cycle length.

To compute the expected cycle length note that these random mappings
are sets of cycles of trees having combinatorial specification

$$\mathfrak{P} \left(\sum_{q\ge 1} \mathfrak{C}_{=q}(\mathcal{T}(\mathcal{Z}))\right).$$

Now a tree on $n$ nodes that goes into a cycle of size $q$ contributes
$nq$ to the total count so we get the species
$$\mathfrak{P} \left(\sum_{q\ge 1} \mathfrak{C}_{=q}(\mathcal{T}(\mathcal{V}^q\mathcal{Z}))\right).$$

It follows that the bivariate generating function of mappings by node
count and cycle size is
$$G(z, v) = \exp\left(\sum_{q\ge 1} \frac{T(v^q z)^q}{q}\right).$$

This yields for the generating function $H(z)$ of the expected cycle size
$$H(z) = \left.\frac{\partial}{\partial v} G(z,v)\right|_{v=1}.$$

This works out to
$$H(z) = \left. \exp\left(\sum_{q\ge 1} \frac{T(v^q z)^q}{q}\right) \left(\sum_{q\ge 1} \frac{qT(v^q z)^{q-1} T'(v^q z)q v^{q-1} z}{q}\right) \right|_{v=1} \\ = \exp\left(\sum_{q\ge 1} \frac{T(z)^q}{q}\right) \left(\sum_{q\ge 1} T(z)^{q-1} T'(z)q z\right) \\ = \frac{z T'(z)}{(1-T(z))^2} \exp\log\frac{1}{1-T(z)} \\ = \frac{z T'(z)}{(1-T(z))^3}.$$

We get from the functional equation
$$T'(z) = \exp(T(z)) + z \exp(T(z)) T'(z)$$
so that
$$T'(z) = \frac{\exp(T(z))}{1-z\exp(T(z))} = \frac{T(z)/z}{1-zT(z)/z} = \frac{1}{z} \frac{T(z)}{1-T(z)}$$
and therefore
$$H(z) = \frac{T(z)}{(1-T(z))^4}.$$

Extracting coefficients via Lagrange inversion we have
$$Q_n = n! [z^n] H(z) = n! \frac{1}{2\pi i} \int_{|z|=\epsilon} \frac{1}{z^{n+1}} \frac{T(z)}{(1-T(z))^4} dz.$$

Put $T(z)=w$ so that $z=w/\exp(w) = w\exp(-w)$ and
$dz = \exp(-w) – w\exp(-w)$
to get
$$n! \frac{1}{2\pi i} \int_{|w|=\epsilon} \frac{\exp(w(n+1))}{w^{n+1}} \frac{w}{(1-w)^4} (\exp(-w) – w\exp(-w)) dw \\ = n! \frac{1}{2\pi i} \int_{|w|=\epsilon} \frac{\exp(wn)}{w^{n+1}} \frac{w}{(1-w)^4} (1 – w) dw \\ = n! \frac{1}{2\pi i} \int_{|w|=\epsilon} \frac{\exp(wn)}{w^{n}} \frac{1}{(1-w)^3} dw.$$

This gives the closed form
$$Q_n = \frac{1}{2} n! \sum_{q=0}^{n-1} \frac{n^q}{q!} (n+1-q) (n-q).$$

The average in question is
$$\frac{Q_n}{n^n \times n}.$$

The sequence $Q_n$ starts with
$$1, 10, 117, 1648, 27425, 528336, 11581885, \\ 284878336, 7772592897, 233010784000,\ldots$$

The Maple code for verification by total enumeration of this sequence
was as follows.

Q :=
proc(n)
option remember;
local ind, d, gf, pos, q, x, seen, traj, cycinit;

if n = 1 then return v fi;

gf := 0;

for ind from n^n to 2*n^n-1 do
d := convert(ind, base, n);
d := map(l->l+1, [seq(d[q], q=1..n)]);

q := 0;
for pos to n do
seen := {}; x := pos; traj := [];

while not(x in seen) do
traj := [op(traj), x];
seen := seen union {x};

x := d[x];
od;

cycinit := 1;
while traj[cycinit] <> x do
cycinit := cycinit + 1;
od;

q := q + nops(traj)-cycinit+1;
od;

gf := gf+v^q;
od;

gf;
end;

EX :=
proc(n)
local T;

T := solve(TT=z*exp(TT), TT);
n!*coeftayl(T/(1-T)^4, z=0, n);
end;

EX2 :=
proc(n)
n! * residue(exp(w*n)/w^n*1/(1-w)^3, w=0);
end;

EX3 :=
proc(n)
end;



Tail length.

This requires a modification to the tree function in order to count
the total tail length for all nodes in the tree.

We obtain the functional equation
$$T(z, v) = z\sum_{q\ge 0} \frac{T(vz,v)^q}{q!} = z\exp(T(vz, v)).$$

This is because when we attach a set of trees to the new root all
nodes in the tree have their tail length incremented by one.

We then have the a simple species for average tail lengths:
$$\mathfrak{P} \left(\mathfrak{C}(\mathcal{T})\right).$$

It follows that the bivariate generating function of mappings by node
count and tail length is
$$G(z, v) = \exp\log\frac{1}{1-T(z,v)} = \frac{1}{1-T(z,v)}.$$

This yields for the generating function $H(z)$ of the expected tail
length (same as before)
$$H(z) = \left.\frac{\partial}{\partial v} G(z,v)\right|_{v=1}.$$

This works out to
$$H(z) = \left.\frac{1}{(1-T(z,v))^2} \frac{\partial}{\partial v} T(z,v) \right|_{v=1} = \frac{1}{(1-T(z,v))^2} \left.z\exp T(vz, v) \left(z \frac{\partial}{\partial z} T(z,v)+ \frac{\partial}{\partial v} T(z,v) \right)\right|_{v=1} \\ = \frac{T(z)}{(1-T(z))^2} (z T'(z) + H(z) (1-T(z))^2) \\ = \frac{z T(z) T'(z)}{(1-T(z))^2} + H(z) T(z).$$

This yields
$$H(z) = \frac{z T(z) T'(z)}{(1-T(z))^3} = \frac{T(z)^2}{(1-T(z))^4}.$$

The Lagrange inversion computation can be carried out as before with
an extra $w$ in the integrand and it produces
$$Q_n = \frac{1}{2} n! \sum_{q=0}^{n-2} \frac{n^q}{q!} (n-q) (n-1-q).$$

The sequence $Q_n$ starts with
$$0, 2, 36, 624, 11800, 248400, 5817084, 150660608, \\ 4285808496, 133010784000,\ldots$$

The Maple code for verification by total enumeration of this sequence
was as follows.

Q :=
proc(n)
option remember;
local ind, d, gf, pos, q, x, seen, traj, cycinit;

if n = 1 then return 1 fi;

gf := 0;

for ind from n^n to 2*n^n-1 do
d := convert(ind, base, n);
d := map(l->l+1, [seq(d[q], q=1..n)]);

q := 0;
for pos to n do
seen := {}; x := pos; traj := [];

while not(x in seen) do
traj := [op(traj), x];
seen := seen union {x};

x := d[x];
od;

cycinit := 1;
while traj[cycinit] <> x do
cycinit := cycinit + 1;
od;

q := q + cycinit-1;
od;

gf := gf+v^q;
od;

gf;
end;

EX :=
proc(n)
local T;

T := solve(TT=z*exp(TT), TT);
n!*coeftayl(T^2/(1-T)^4, z=0, n);
end;

EX2 :=
proc(n)
n! * residue(exp(w*n)/w^(n-1)*1/(1-w)^3, w=0);
end;

EX3 :=
proc(n)
end;


The labelled tree function recently appeared at this
and at this
which is closely related to the present subject.

Cycle size plus tail length.

We will show that with these parameters being cumulative we are indeed
justified in adding the generating functions for the two cases that we
considered separately above. This matches what is being stated in the
cited paper.

Using the same notation as in the companion answer we get for the
generating function

$$G(z, v) = \exp\left(\sum_{q\ge 1} \frac{T(v^q z, v)^q}{q}\right).$$

where $T(z,v)$ is the generating function from the tail length
computation.

This yields for the generating function $H(z)$ of the expected cycle
size plus tail length same as in the other two answers
$$H(z) = \left.\frac{\partial}{\partial v} G(z,v)\right|_{v=1}.$$

This works out to
$$H(z) = \left. \exp\left(\sum_{q\ge 1} \frac{T(v^q z, v)^q}{q}\right) \\ \times \left(\sum_{q\ge 1} \frac{qT(v^q z)^{q-1} \left(qz v^{q-1}\frac{\partial}{\partial z} T(z,v) + \frac{\partial}{\partial v} T(z, v)\right)}{q}\right) \right|_{v=1}.$$

Put $$S(z) = \left.\frac{\partial}{\partial v} T(z,v) \right|_{v=1}$$

and use the functional equation to obtain
$$\left.\frac{\partial}{\partial v} T(z,v) \right|_{v=1} = \left.z\exp T(vz, v) \left(z \frac{\partial}{\partial z} T(z,v)+ \frac{\partial}{\partial v} T(z,v) \right)\right|_{v=1} \\ = T(z) (z T'(z) + S(z)) = z T(z) T'(z) + T(z) S(z)$$

so that
$$S(z) = \frac{z T(z) T'(z)}{1-T(z)} = \frac{T(z)^2}{(1-T(z))^2}.$$

Entering this into the equation for $H(z)$ we find
$$H(z) = \exp\left(\sum_{q\ge 1} \frac{T(z)^q}{q}\right) \left(\sum_{q\ge 1} T(z)^{q-1} \left(T'(z)q z + \frac{T(z)^2}{(1-T(z))^2}\right)\right) \\ = \left(\frac{z T'(z)}{(1-T(z))^2} + \frac{T(z)^2}{(1-T(z))^3}\right) \exp\log\frac{1}{1-T(z)} \\ = \left(\frac{T(z)+T(z)^2}{(1-T(z))^3}\right) \exp\log\frac{1}{1-T(z)} \\ = \frac{T(z)+T(z)^2}{(1-T(z))^4}.$$

This is the sum of the two generating functions as predicted above.

We get for the closed form
$$Q_n = n! \sum_{q=0}^{n-2} \frac{n^q}{q!} (n-q)^2 + n! \frac{n^{n-1}}{(n-1)!} \\ = n^n + n! \sum_{q=0}^{n-2} \frac{n^q}{q!} (n-q)^2.$$

The sequence starts with
$$1, 12, 153, 2272, 39225, 776736, 17398969, 435538944, \\ 12058401393, 366021568000,\ldots$$

The Maple code for this was as follows where the reader is asked to
note certain optimizations that have been made in comparison to the

Q :=
proc(n)
option remember;
local ind, d, gf, pos, q, x, seen, traj;

if n = 1 then return v fi;

gf := 0;

for ind from n^n to 2*n^n-1 do
d := convert(ind, base, n);
d := map(l->l+1, [seq(d[q], q=1..n)]);

q := 0;
for pos to n do
x := pos; traj := [];

do
for seen to nops(traj) do
if traj[seen] = x then break fi;
od;

if seen <= nops(traj) then break fi;

traj := [op(traj), x];
x := d[x];
od;

q := q + nops(traj);
od;

gf := gf+v^q;
od;

gf;
end;

EX :=
proc(n)
local T;

T := solve(TT=z*exp(TT), TT);
n!*coeftayl((T+T^2)/(1-T)^4, z=0, n);
end;

EX2 :=
proc(n)
n! * residue(exp(w*n)*(1/w^(n-1)+1/w^n)*1/(1-w)^3, w=0);
end;

EX3 :=
proc(n)
n^n + n! * add(n^q/q!*(n-q)^2, q=0..n-2);
end;